Elephants, crops and people in Ushasha Sector, southern Queen Elizabeth National Park, Uganda - Michael Keigwin (Pachyderm)
Reviews the implementation and ongoing programme of the Elephants, Crops and People (ECP) project in the southern section of Queen Elizabeth NP which assesses the status of elephants, and works in cooperation with the Uganda Wildlife Authority and local farmers to find ways to mitigate elephant-human conflict interactions. The monitoring programme was based on the standardized interaction monitoring system used in Virunga NP. During the first month over 150 separate crop-raiding incidents recorded. All occurred at night, bull, family groups and large aggregations, sometimes numbering over 150 animals. Results indicate most incidents happen during the wet season when elephants come into the Park by crossing the Ishasha River, the boundary between Uganda and Democratic Republic of Congo in this area. The transmigration route is monitored by a EPC team walking the 25 km stretch of the Ishasa River and recording evidence of elephants at crossing places. Although the aggregations are large, the old animals are few, and the animals show some fear the population contains an abundance of young and subadults and appears to be increasing. Monitoring and research work continue.